G404(P) Transcutaneous Electrical Nerve Stimulation for the treatment for bladder overactivity in Paediatric patients resistant or intolerant to anti-cholinergic medication. (7th April 2014) - Moore, E; Wright, A; Clothier, J
Abstract : Aims: To describe our single centre experience of the use of transcutaneous electrical nerve stimulation (TENS) as a form of neuromodulation for the treatment of bladder over activity (OAB) in children resistant or intolerant to anti-cholinergic therapy. Methods: All patients over the age of 5 years with a diagnosis of OAB who were found to be anti-cholinergic intolerant or resistant (following treatment with ≥2 anti-cholinergic medications) were offered TENS therapy. All patients had been given a diagnosis of OAB following bladder clinic consultation, completed bladder diaries and assessment with 3 voids on the uroflow with post void ultrasound. All were individually shown how to use the TENS machine and were commenced on a 3 month program involving, daily 40-60 min therapy at home. Treatment diaries were given with review organised at the end of 3 months of treatment. Results: 42 children received treatment between July 2012 and October 2013. 67% female. Median age 11 years (range 6–17 years). 90% were resistant to anti-cholinergic treatment, with 7 previously receiving intra-vesical botulinum toxin injection for OAB. Cure of symptoms was achieved in 21%, improvement in symptoms seen in 43%, 31% had no response, 1 did not commence therapy due to discomfort and 1 lost to follow up. 88% found the treatment acceptable, 2 patients described discomfort, 2 received shocks and 1 found treatment too time consuming. Conclusions: TENS offers a well tolerated and effective treatment option for children with anti-cholinergic resistant/intolerant OAB. Large randomised studies are required to determine the population this treatment benefits the most and longer follow-up required to determine if improvement is sustained once treatment is discontinued.